Renin-Angiotensin System Inhibitors in COVID-19: Current Concepts - Kunal Mahajan; Prakash Chand Negi; Neeraj Ganju; Sachin Sondhi; Naresh Gaur; Rao Somendra (International Journal of Hypertension)
The functional receptor to SARS-CoV-2, the virus responsible for the coronavirus disease 2019 (COVID-19) pandemic, is angiotensin-converting enzyme-2 (ACE-2), the same enzyme that physiologically counters the renin-angiotensin system (RAS) activation. Some researchers have questioned RAS inhibitors’ safety in COVID-19 patients since these drugs have demonstrated an increase in ACE-2 expression in preclinical studies; therefore, they may facilitate viral invasion. On the contrary, others have hypothesized a protective role of RAS inhibitors against COVID-19-associated lung injury. Overall, the data are grossly inadequate to reach any conclusion since no human trials have yet evaluated the effects of RAS inhibitors in COVID-19. We review the current data and pathophysiological mechanisms behind this intriguing interplay between the RAS inhibitors and the COVID-19.